Promoting inclusion in ecological field experiences: Examining and overcoming barriers to a professional rite of passage. Issue 4 (20th July 2020) - Morales, Nia; Bisbee O'Connell, Kari; McNulty, Stacy; Berkowitz, Alan; Bowser, Gillian; Giamellaro, Michael; Miriti, Maria N.
Abstract: Field experiences can provide transformative opportunities for many individuals who eventually pursue ecology, natural resource, and conservation careers. However, some of the same elements of field‐based programs that define and provide pivotal experiences for some represent barriers for others, especially students from underrepresented groups. Barriers may be financial, physical, cultural, or social. Issues of gender, identity, and race/ethnicity, for example, can be isolating or shut down learning during intensive field experiences when group leaders are not prepared to respond to interpersonal challenges. We explore some benefits and barriers presented by field learning experiences as well as some challenges and potential strategies to broaden inclusivity with the hope of encouraging further conversation on diversity and inclusion in field experiences.